Two-dimensional dysprosium(III) coordination polymer: Structure, single-molecule magnetic behavior, proton conduction, and luminescence - Chen, Jin-Fen; Ge, Yi-Liang; Wu, Dong-Hui; Cui, Hao-Tian; Mu, Zhi-Lin; Xiao, Hong-Ping; Li, Xinhua; Ge, Jing-Yuan (Frontiers in Chemistry, 2022)
A new dysprosium(III) coordination polymer, [Dy(Hm-dobdc)(H2O)2]·H2O (Dy-CP), was hydrothermal synthesized based on 4,6-dioxido-1,3-benzenedicarboxylate (H4m-dobdc) ligand containing carboxyl and phenolic hydroxyl groups. The Dy(III) center adopts an octa-coordinated [DyO8] geometry, which can be described as a twisted square antiprism (D4d symmetry). Neighboring Dy(III) ions are interconnected by deprotonated Hm-dobdc3− ligand to form the two-dimensional infinite layers, which are further linked to generate three-dimensional structure through abundant hydrogen bonds mediated primarily by coordinated and lattice H2O molecules. Magnetic studies demonstrates that Dy-CP shows the field-induced slow relaxation of magnetization and the energy barrier Ueff/kB and relaxation time τ0 are 35.3 K and 1.31×10−6 s, respectively. Following the vehicular mechanism, Dy-CP displays proton conductivity with σ equal to 7.77×10-8 S cm-1 at 353 K and 30%RH. Moreover, luminescence spectra reveal that H4m-dobdc can sensitize characteristic luminescence of Dy(III) ion. Herein, good magnetism, proton conduction, and luminescence are simultaneously achieved, and thus, Dy-CP is a potential multifunctional coordination polymer material.